Energy balance of indirect reaction gas turbine engine - Терещенко, Ю. М.; Волинська, Л. Г.; Бондарчук, В. А. (Proceedings of National Aviation University, 2021)
Energy balance is considered and the formula for calculation efficiency of indirect reaction gas turbine engine is deduced in the article.